Method for modifying potato starch and modified potato starch

CN122879356APending Publication Date: 2026-10-09XINGHE MINGXING AGRI & ANIMAL HUSBANDRY DEV CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202610995218.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-06
Publication Date
2026-10-09

AI Technical Summary

Technical Problem

抗性马铃薯淀粉因来源稳定、产量较高、生理功能突出,成为马铃薯深加工领域重点开发的方向,但天然抗性马铃薯淀粉在实际应用中存在明显短板,其水溶性、膨胀度等基础理化性质较差,糊化温度偏高,难以适配现代食品工业连续化、高温化、高剪切化的加工条件,同时天然淀粉中抗性淀粉含量偏低,保健功能无法充分发挥,且在加工过程中易受热、受力降解,结构稳定性不足,严重限制了其在高端食品领域的规模化应用

Benefits of technology

1)本申请中,采用超声-酶解-交联三元联合改性的方式对抗性马铃薯淀粉进行改性,可有效提升原抗性马铃薯淀粉中抗性淀粉的含量,同时提升其热稳定性、机械稳定性,从而使得抗性马铃薯淀粉的综合功能性和稳定性得到有效提升。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The application provides a modified method of potato starch and modified potato starch. The method of the application adopts a ternary combined modification mode of ultrasonic-enzymolysis-crosslinking to modify resistant potato starch, so that the content of resistant starch in the original resistant potato starch is effectively improved, and the thermal stability and mechanical stability of the resistant potato starch are improved, thereby the comprehensive functionality and stability of the resistant potato starch are effectively improved. The modified potato starch provided by the application has the characteristics of high resistant starch content, good thermal stability and good shear resistance, and is suitable for high-temperature and high-shear processing scenes.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application relates to the field of starch modification technology, and in particular to a method for modifying potato starch and modified potato starch. Background Technology

[0002] Currently, my country's potato industry is at a critical stage of transformation from primary processing to intensive processing. Resistant starch, as a high-quality raw material with both nutritional and processing application value, is experiencing a continuous increase in market demand in functional foods, health drinks, and special medical foods. Due to its stable source, high yield, and outstanding physiological functions, resistant potato starch has become a key development direction in the field of potato deep processing. However, natural resistant potato starch has significant shortcomings in practical applications. Its basic physicochemical properties, such as water solubility and swelling, are poor, and its gelatinization temperature is too high, making it difficult to adapt to the continuous, high-temperature, and high-shear processing conditions of modern food industry. Furthermore, the resistant starch content in natural starch is relatively low, preventing the full realization of its health benefits. It is also easily degraded by heat and stress during processing, resulting in insufficient structural stability, which severely limits its large-scale application in the high-end food sector. Summary of the Invention

[0003] This application provides a method for modifying potato starch and modified potato starch to solve the problems mentioned in the background art.

[0004] In a first aspect, this application provides a method for modifying potato starch, comprising the following steps: The resistant potato starch and water are mixed evenly and pre-dispersed to obtain resistant potato starch milk. The resistant potato starch milk was subjected to ultrasonic treatment and a first post-treatment in sequence to obtain the first starch. The first starch and water are mixed evenly and then pre-dispersed to obtain the first starch milk; The first starch milk was subjected to enzymatic hydrolysis and a second post-treatment in sequence to obtain the second starch. The second starch and water are mixed evenly, and a third pre-dispersion is performed to obtain the second starch milk; A cross-linking agent is added to the second starch milk to carry out a cross-linking reaction, followed by a third post-treatment to obtain modified potato starch.

[0005] Optionally, the first pre-dispersion operation process is as follows: After mixing resistant potato starch and water evenly, the pH of the system is adjusted to neutral using an acid-base regulator, and then stirred at a constant temperature of 38-42℃ for 8-12 minutes to obtain resistant potato starch milk. The acid-base regulator is an aqueous solution of an inorganic acid and an inorganic base; The concentration of the resistant potato starch milk is 8-12%; The resistant potato starch contains >50% resistant starch.

[0006] Optionally, the ultrasonic treatment process is as follows: The resistant potato starch milk was placed in an ultrasonic processor and ultrasonically treated for 28-32 minutes under stirring conditions to obtain ultrasonically treated starch milk. During the ultrasonic treatment, the ultrasonic power is 200~400w, the ultrasonic frequency is 20~40kHz, and the temperature of the resistant potato starch milk is controlled at 38~42℃.

[0007] Optionally, the first post-processing operation is as follows: The ultrasonically treated starch milk was heated in a bath at 95-102℃ for 15-20 minutes, then cooled to room temperature, and centrifuged at 3000-4000 rpm for 8-12 minutes to obtain the first centrifugal precipitate. The first centrifugal precipitate was washed with anhydrous ethanol until no sugar residue was found, and then dried in an oven at 58-62℃ until constant weight. After drying, the first centrifuged precipitate is crushed and passed through an 80-mesh sieve. The material passing through the sieve is collected, which is the first starch.

[0008] Optionally, the second pre-dispersion operation process is as follows: After mixing the first starch and water evenly, the pH of the system is adjusted to the first weak acidity using an acid-base regulator, and then stirred at a constant temperature of 53~57℃ for 8~12 minutes to obtain the first starch milk. The acid-base regulator is an aqueous solution of an inorganic acid and an inorganic base; The first weak acidity is pH = 6.0 ± 0.1; The concentration of the first starch milk is 8-12%.

[0009] Optionally, the enzymatic hydrolysis process is as follows: Add the enzyme preparation to the first starch milk and mix well. Stir at a constant temperature of 54-56℃ for 20-40 minutes to obtain the enzymatic hydrolysate. The enzyme preparation is a mixture of α-amylase and saccharifying enzyme, wherein the amount of α-amylase is 2.0~2.5 U / mg dry starch and the amount of saccharifying enzyme is 2.8~3.0 U / mg dry starch.

[0010] Optionally, the second post-processing operation is as follows: Heat the enzymatic hydrolysate in a bath at 95-102℃ for 10-15 minutes, then cool it to room temperature. Centrifuge it at 3000-4000 rpm for 8-12 minutes to obtain a second centrifugal precipitate. Wash the second centrifugal precipitate with anhydrous ethanol until no sugar residue remains. Then dry the washed second centrifugal precipitate in an oven at 58-62℃ until constant weight. After drying, the first centrifuged precipitate is crushed and passed through an 80-mesh sieve. The material passing through the sieve is collected, which is the second starch.

[0011] Optionally, the third pre-dispersion operation process is as follows: After mixing the second starch and water evenly, the pH of the system is adjusted to a slightly acidic level using an acid-base regulator. Then, the mixture is stirred at a constant temperature of 43-47℃ for 8-12 minutes to obtain the second starch milk. The acid-base regulator is an aqueous solution of an inorganic acid and an inorganic base; The second weak acidity is pH = 5.0 ± 0.1; The concentration of the second starch milk is 8-12%.

[0012] Optionally, the crosslinking reaction is performed as follows: The second starch milk and the crosslinking agent were mixed evenly and stirred at a reaction temperature of 42~48℃ for 0.8~1.2h. The pH of the reaction system was then adjusted to neutral with alkali to obtain the crosslinking reaction solution. The amount of the crosslinking agent used is 0.10~0.20% of the dry starch content in the second starch milk; The crosslinking agent is one or more of phosphorus oxychloride, malic acid, malonic acid, citric acid, and tartaric acid. The alkali is an inorganic alkali or an aqueous solution of an inorganic alkali; The third post-processing operation is as follows: The cross-linking reaction solution was heated in a bath at 95-102℃ for 8-12 minutes, cooled to room temperature, and centrifuged at 3000-4000 rpm for 8-12 minutes to obtain the third centrifugal precipitate. The third centrifugal precipitate was washed with anhydrous ethanol until no sugar residue was found, and then dried in an oven at 58-62℃ until constant weight. After drying, the first centrifuged sediment is crushed and passed through an 80-mesh sieve. The material passing through the sieve is collected, which is the modified potato starch.

[0013] Secondly, this application provides a modified potato starch, comprising a starch prepared by the method described in any one of the first aspects above.

[0014] The method described in this application has the following beneficial effects: 1) In this application, the resistant potato starch is modified by a combination of ultrasonic-enzymatic hydrolysis-crosslinking ternary modification method, which can effectively increase the content of resistant starch in the original resistant potato starch, while improving its thermal stability and mechanical stability, thereby effectively improving the comprehensive functionality and stability of the resistant potato starch.

[0015] 2) In the method of this application, ultrasonic physical modification, enzymatic biological modification, and cross-linking chemical modification are combined in an orderly manner according to their mechanisms of action to construct a ternary composite modification system that is progressive and synergistic. Ultrasonic modification is responsible for loosening the starch structure and providing more reaction sites for enzymatic hydrolysis. Enzymatic modification is responsible for directional optimization of molecular structure and increasing resistant starch content. Cross-linking modification is responsible for stabilizing molecular structure and enhancing processing stability. The three modification methods complement each other and have superimposed effects, which completely solves the industry problem that single modification cannot simultaneously achieve high resistant starch content, good physicochemical properties and strong processing stability. The modification effect is far superior to that of single modification technology.

[0016] 3) The potato starch modification method provided in this application specifically improves the processing adaptability of starch. The modified starch not only has a significantly increased resistant starch content, but also has excellent thermal and mechanical stability. It can be widely used in high-temperature and high-shear processing scenarios such as baking, beverages, and health foods, breaking the traditional limitation of resistant starch application scenarios. At the same time, the process equipment used in the project is conventional, the additives meet food-grade standards, and the production cost is controllable. The technical results can be directly transformed and applied without the need for large-scale equipment modification by enterprises, which greatly reduces the industrialization threshold. It can effectively help enterprises develop high-end functional starch products, enhance market competitiveness, and provide a replicable and scalable modification technology path for the potato deep processing industry. Detailed Implementation

[0018] To make the objectives, technical solutions, and advantages of the embodiments of this application clearer, the technical solutions in the embodiments of this application are described clearly and completely below. Obviously, the described embodiments are only some embodiments of this application, not all embodiments. Based on the embodiments in this application, all other embodiments obtained by those skilled in the art without creative effort are also within the scope of protection of this application.

[0019] In a first aspect, this application provides a method for modifying potato starch, comprising the following steps: The resistant potato starch and water are mixed evenly and pre-dispersed to obtain resistant potato starch milk. In this application, the purpose of the first pre-dispersion is to enable the resistant potato starch to be uniformly dispersed in water (the water used here and in the following processes is deionized or distilled water).

[0020] The resistant potato starch milk was subjected to ultrasonic treatment and a first post-treatment in sequence to obtain the first starch. The first starch and water are mixed evenly and then pre-dispersed to obtain the first starch milk; The first starch milk was subjected to enzymatic hydrolysis and a second post-treatment in sequence to obtain the second starch. The second starch and water are mixed evenly, and a third pre-dispersion is performed to obtain the second starch milk; A cross-linking agent is added to the second starch milk to carry out a cross-linking reaction, followed by a third post-treatment to obtain modified potato starch.

[0021] Optionally, the first pre-dispersion operation process is as follows: After mixing resistant potato starch and water evenly, the pH of the system is adjusted to neutral using an acid-base regulator, and then stirred at a constant temperature of 38-42℃ for 8-12 minutes to obtain resistant potato starch milk. The acid-base regulator is an aqueous solution of an inorganic acid and an inorganic base; The concentration of the resistant potato starch milk is 8-12%; The resistant potato starch contains >50% resistant starch.

[0022] In this application, the acid-base regulator is an aqueous solution of an inorganic acid and an inorganic base. The inorganic acid can be hydrochloric acid or sulfuric acid, for example, hydrochloric acid. The inorganic base can be one or more of sodium hydroxide, potassium hydroxide, sodium carbonate, potassium carbonate, sodium bicarbonate, and potassium bicarbonate, for example, sodium hydroxide. The concentration of the aqueous solution of the inorganic acid can be 5-15%, and the concentration of the aqueous solution of the inorganic base can be 5-15%, or other achievable concentrations.

[0023] In this application, the pH is neutral. In practice, it should be controlled at pH=7.0±0.1 to adjust the starch milk system to neutral to avoid deviations in experimental results due to differences in the acidity or alkalinity of the system during ultrasonication. Ultrasonic treatment under acidic conditions may activate starch and cause hydrolysis, resulting in a decrease in the content of resistant starch in the final product. Ultrasonic treatment under alkaline conditions may cause some starch to gelatinize prematurely, affecting the experimental results and causing misjudgment.

[0024] In this application, the mixed starch milk is stirred at a constant temperature of 38~42℃ for 8~12 minutes. This treatment allows the starch to fully swell and disperse. Too low a temperature may result in incomplete starch swelling, while too high a temperature may cause starch gelatinization, affecting the treatment results.

[0025] In this application, the concentration of resistant potato starch milk is 8-12%. This is because using this concentration of starch milk makes the ultrasonic treatment process of the starch milk controllable. If the concentration is too high, the starch is prone to agglomeration during the ultrasonic process, which affects the ultrasonic effect. If the concentration is too low, the starch particles will be more easily broken due to the cavitation effect of the ultrasonic waves, making it difficult to control the treatment process.

[0026] In this application, the resistant potato starch contains >50% resistant starch. This is because under these conditions, the starch granules possess certain crystalline regions. These crystalline regions act as inert templates, and the modification only alters the amorphous regions (i.e., the digestible starch regions) without disrupting the ordered structure. Furthermore, the crystalline regions can control the subsequent enzymatic hydrolysis rate and also exhibit a certain degree of hydrothermal stability. Selecting starch with a resistant starch content >50% for modification essentially utilizes the inherently highly ordered condensed state of the raw material as a protective framework, and through interfacial confinement reactions, directionally modifies the amorphous regions, thereby obtaining a composite starch that is thermodynamically stable, has enhanced enzyme kinetic barriers, and is rich in functional crystalline regions.

[0027] The stirring speed used in obtaining resistant potato starch milk is, for example, 60-80 rpm.

[0028] Optionally, the ultrasonic treatment process is as follows: The resistant potato starch milk was placed in an ultrasonic processor and ultrasonically treated for 28-32 minutes under stirring conditions to obtain ultrasonically treated starch milk. During the ultrasonic treatment, the ultrasonic power is 200~400w, the ultrasonic frequency is 20~40kHz, and the temperature of the resistant potato starch milk is controlled at 38~42℃.

[0029] In this application, appropriate ultrasonic treatment can induce mechanical damage, selectively breaking the α-1,6 glycosidic bonds of amylopectin and reducing its molecular weight (e.g., from approximately 195 kDa to 157 kDa). This degradation increases the content of amylose and the proportion of short-chain free starch, which is beneficial for subsequent enzymatic hydrolysis and cross-linking processes. On the other hand, ultrasound-induced multi-scale rearrangement can generate new V-shaped resistant crystals, thereby increasing the content of resistant starch. In summary, in this application, the microscopic impact force generated by the cavitation effect of ultrasonic treatment can disrupt the surface structure and intermolecular hydrogen bonds of starch granules, moderately loosening the starch crystalline regions. Without introducing chemical substances, this improves the water solubility and swelling properties of starch, initially increasing the content of resistant starch, while lowering the gelatinization temperature, providing a more reactive starch structure for subsequent enzymatic hydrolysis. Moreover, ultrasonic treatment is characterized by mild conditions, simple operation, and high safety, meeting the safety standards for food processing.

[0030] In this application, when the ultrasonic power is below 200W, the ultrasonic energy is insufficient to fully break down the intermolecular hydrogen bonds and crystalline structure of starch, resulting in fewer amorphous regions on the surface of starch granules and a slow increase in resistant starch content. On the other hand, excessively high ultrasonic power can cause starch molecular chains to break, the crystalline structure to be excessively destroyed, and some resistant starch to be converted into digestible starch, leading to a decrease in resistant starch content.

[0031] The temperature during the ultrasonic process is controlled at 38~42℃ for two reasons: firstly, starch has better dispersibility at this temperature; and secondly, it can avoid starch gelatinization and other adverse effects caused by the heat generated during ultrasonication.

[0032] Stirring is also required during the ultrasound process to prevent starch from agglomerating. The stirring speed is, for example, 50-60 rpm.

[0033] Optionally, the first post-processing operation is as follows: The ultrasonically treated starch milk was heated in a bath at 95-102℃ for 15-20 minutes, then cooled to room temperature, and centrifuged at 3000-4000 rpm for 8-12 minutes to obtain the first centrifugal precipitate. The first centrifugal precipitate was washed with anhydrous ethanol until no sugar residue was found, and then dried in an oven at 58-62℃ until constant weight. After drying, the first centrifuged precipitate is crushed and passed through an 80-mesh sieve. The material passing through the sieve is collected, which is the first starch.

[0034] In this application, during the first post-treatment, heating is performed at a bath temperature of 95-102°C. The heating medium for this process can be a heat-conducting sand, heat-conducting oil, water, or any other medium capable of achieving this temperature. Heating at this temperature raises the temperature of the ultrasonicated system above the starch gelatinization temperature, providing a thermodynamic threshold to overcome the nucleation and growth barriers required for amylose crystallization, causing the amylopectin to disintegrate, expand, and completely release the amylose chains. The short-chain starch molecules pre-destroyed and activated by ultrasonic pretreatment are more easily rearranged through hydrogen bonds during cooling and regeneration, forming a dense, enzyme-resistant structure, which can effectively increase the resistant starch content.

[0035] In this application, centrifugation at 3000-4000 rpm for 8-12 minutes can effectively separate the ultrasonically treated starch, thereby avoiding the precipitation of large amounts of soluble sugars, short-chain dextrins and small molecule impurities (such as maltose and glucose) after ultrasonic treatment. This greatly improves the starch recovery rate, reduces starch loss, and reduces interference from the above-mentioned small molecule substances.

[0036] The purpose of washing with anhydrous ethanol in this application is to replace the water in the precipitate with ethanol, reduce the water activity, inhibit the resolution or swelling of starch molecules, and at the same time dissolve and remove residual soluble sugars, short-chain dextrins, and small molecule impurities (such as maltose and glucose), ensuring the chemical purity of the product. Meanwhile, as a non-solvent, ethanol can induce the further ordered arrangement of hydrogen bonds between starch chains, promote the transformation of some amorphous regions into denser anti-enzymatic crystals (such as V-shaped crystals), thereby increasing the yield of resistant starch. In addition, because ethanol evaporates quickly, the precipitate after washing is easy to dry at low temperature, avoiding browning or secondary gelatinization caused by high-temperature drying.

[0037] The dried first centrifugal precipitate is crushed and passed through an 80-mesh sieve. The undersize material is collected to reduce the particle size of the first centrifugal precipitate through crushing, thereby obtaining starch with a particle size smaller than 80 mesh, which facilitates better dispersion of the starch in subsequent operations. Meanwhile, the oversize material should be returned to the crushing process for further crushing.

[0038] Optionally, the second pre-dispersion operation process is as follows: After mixing the first starch and water evenly, the pH of the system is adjusted to the first weak acidity using an acid-base regulator, and then stirred at a constant temperature of 53~57℃ for 8~12 minutes to obtain the first starch milk. The acid-base regulator is an aqueous solution of an inorganic acid and an inorganic base; The first weak acidity is pH = 6.0 ± 0.1; The concentration of the first starch milk is 8-12%.

[0039] In this application, the pH of the first starch milk is adjusted to a weakly acidic pH of 6.0 ± 0.1 because this pH is the optimal pH condition for the enzyme in the enzyme preparation to exert its catalytic activity. The principles for setting the parameters of other operations in this step, such as dispersion and preheating, are the same as those for the first pre-dispersion described above, and will not be repeated here.

[0040] Optionally, the enzymatic hydrolysis process is as follows: Add the enzyme preparation to the first starch milk and mix well. Stir at a constant temperature of 54-56℃ for 20-40 minutes to obtain the enzymatic hydrolysate. The enzyme preparation is a mixture of α-amylase and saccharifying enzyme, wherein the amount of α-amylase is 2.0~2.5 U / mg dry starch and the amount of saccharifying enzyme is 2.8~3.0 U / mg dry starch.

[0041] In this application, the enzymatic hydrolysis temperature of 54~56℃ is the optimal temperature for the enzyme in the enzyme preparation to exert its catalytic effect.

[0042] The co-hydrolysis of resistant starch using α-amylase and saccharifying enzyme is a multi-enzyme synergistic catalytic approach. α-amylase randomly endocleaves α-1,4 glycosidic bonds, breaking down the crystalline structure of resistant starch into short-chain dextrins, creating more substrate sites for the saccharifying enzyme. The saccharifying enzyme, on the other hand, exocleaves α-1,4 and α-1,6 glycosidic bonds from the non-reducing ends of dextrins and maltodextrins, continuously releasing glucose. This functional complementarity enables a cascaded amplification of steric hindrance dismantling and complete saccharification, significantly improving hydrolysis efficiency.

[0043] The choice of a weakly acidic pH of 6.0 ± 0.1 is based on the overlap in the pH responses of the two enzymes. The catalytic activity of both enzymes is better utilized under these conditions. This allows for a single-tank process where α-amylase and saccharifying enzyme act simultaneously. This operation avoids the need for separate pH adjustments during the liquefaction and saccharification stages in traditional processes, reducing reagent consumption and ion introduction.

[0044] Optionally, the second post-processing operation is as follows: Heat the enzymatic hydrolysate in a bath at 95-102℃ for 10-15 minutes, then cool it to room temperature. Centrifuge it at 3000-4000 rpm for 8-12 minutes to obtain a second centrifugal precipitate. Wash the second centrifugal precipitate with anhydrous ethanol until no sugar residue remains. Then dry the washed second centrifugal precipitate in an oven at 58-62℃ until constant weight. After drying, the first centrifuged precipitate is crushed and passed through an 80-mesh sieve. The material passing through the sieve is collected, which is the second starch.

[0045] In this application, the process of the second post-processing operation is roughly the same as that of the first post-processing operation, and the principle is also the same, so it will not be described again.

[0046] Optionally, the third pre-dispersion operation process is as follows: After mixing the second starch and water evenly, the pH of the system is adjusted to a slightly acidic level using an acid-base regulator. Then, the mixture is stirred at a constant temperature of 43-47℃ for 8-12 minutes to obtain the second starch milk. The acid-base regulator is an aqueous solution of an inorganic acid and an inorganic base; The second weak acidity is pH = 5.0 ± 0.1; The concentration of the second starch milk is 8-12%.

[0047] In this application, the second weak acid is pH = 5.0 ± 0.1, because the subsequent crosslinking process needs to be carried out at this pH. The remaining processing procedures and the use of acid-base adjusters are the same as in the first pre-dispersion operation, and will not be described in detail here.

[0048] Optionally, the crosslinking reaction is performed as follows: The second starch milk and the crosslinking agent were mixed evenly and stirred at a reaction temperature of 42~48℃ for 0.8~1.2h. The pH of the reaction system was then adjusted to neutral with alkali to obtain the crosslinking reaction solution. The amount of the crosslinking agent used is 0.10~0.20% of the dry starch content in the second starch milk; The crosslinking agent is one or more of phosphorus oxychloride, malic acid, malonic acid, citric acid, and tartaric acid. The alkali is an inorganic alkali or an aqueous solution of an inorganic alkali; The third post-processing operation is as follows: The cross-linking reaction solution was heated in a bath at 95-102℃ for 8-12 minutes, cooled to room temperature, and centrifuged at 3000-4000 rpm for 8-12 minutes to obtain the third centrifugal precipitate. The third centrifugal precipitate was washed with anhydrous ethanol until no sugar residue was found, and then dried in an oven at 58-62℃ until constant weight. After drying, the first centrifuged sediment is crushed and passed through an 80-mesh sieve. The material passing through the sieve is collected, which is the modified potato starch.

[0049] In this application, the choice of crosslinking agent is not limited to the above-mentioned reagents, and may also be sodium trimetaphosphate, sodium tripolyphosphate, ethylene glycol diglycidyl ether, adipic acid, etc.

[0050] In this application, cross-linking agents are used to treat enzymatically hydrolyzed starch. The core function of this method is to further enhance the product's resistance to digestive enzymes and optimize its process applicability. At the molecular level, the cross-linking reaction occurs through the reaction of the multifunctional groups of the cross-linking agent with the hydroxyl groups in starch molecules to form ether or ester bonds, creating a stable three-dimensional network structure between the hydrolyzed starch molecular chains. This chemical cross-linking network significantly enhances the starch granules' tolerance to external shear forces and acidic environments. Regarding digestibility, the steric hindrance effect significantly reduces the accessibility of α-amylase to glycosidic bonds. The degree of hydrolysis of the modified cross-linked starch is significantly lower than that of starch hydrolyzed by enzyme alone, and the higher the degree of cross-linking, the stronger the resistance to enzymatic hydrolysis. In terms of physicochemical properties, enzymatic hydrolysis increases the specific surface area and porosity of starch, while cross-linking strengthens the mechanical strength of the gel network on this structural basis, further enhancing shear resistance and the ability to inhibit retrogradation. In summary, through the synergistic effect of enzymatic hydrolysis creating pores and cross-linking constructing the network, both digestibility and processing stability are simultaneously improved.

[0051] Furthermore, by chemically cross-linking starch molecules to form stable covalent bonds and constructing a dense three-dimensional network structure, the thermal decomposition temperature and mechanical shear stability of starch are significantly improved, the weight loss and viscosity loss rates during high-temperature and high-shear processing are reduced, and a high resistant starch content is maintained. This balances functionality and processing stability, ultimately forming a complete modification technology that can be directly applied to industrial production. This technology has good repeatability and can stably produce high-quality modified resistant potato starch.

[0052] In this application, during the third post-processing step, the alkali used is an inorganic alkali or an aqueous solution of an inorganic alkali. The inorganic alkali can be one or more of sodium hydroxide, potassium hydroxide, sodium carbonate, potassium carbonate, sodium bicarbonate, and potassium bicarbonate, such as sodium hydroxide. The aqueous solution of the inorganic alkali can be, for example, an aqueous solution of the aforementioned inorganic alkali, with a concentration of 5-15%, or other achievable concentrations.

[0053] The process of the third post-processing operation is roughly the same as that of the first post-processing operation, and the principle is also the same, so it will not be described in detail.

[0054] During the cross-linking reaction, the stirring speed is 100~150 rpm.

[0055] Secondly, this application provides a modified potato starch, comprising a starch prepared by the method described in any one of the first aspects above.

[0056] The modified potato starch provided in this application is processed by a three-stage process of ultrasound, enzymatic hydrolysis, and cross-linking, thus exhibiting high resistant starch content, good thermal stability, and good mechanical stability, making it suitable for processing scenarios involving high temperature and high shear.

[0057] Example 1 A method for modifying potato starch, achieved through the following steps:

[0058] S101. After mixing resistant potato starch and water evenly, the pH of the system is adjusted to neutral by using 5% hydrochloric acid and 5% sodium hydroxide aqueous solution. Then, the mixture is stirred at 50 rpm for 8 minutes at 38°C to obtain 8% resistant potato starch milk.

[0059] S102. Place the resistant potato starch milk in an ultrasonic processor, set the ultrasonic power to 200W, the ultrasonic frequency to 20kHz, and control the temperature of the resistant potato starch milk at 38℃. Under stirring conditions at 60rpm, ultrasonically treat for 28min to obtain ultrasonically treated starch milk.

[0060] S103. The ultrasonically treated starch milk is heated in a bath at 95°C for 20 minutes, then cooled to room temperature, and centrifuged at 3500 rpm for 12 minutes to obtain the first centrifugal precipitate. The first centrifugal precipitate is washed with anhydrous ethanol until no sugar residue is left, and then dried in an oven at 58°C to constant weight.

[0061] After drying, the first centrifuged precipitate is crushed and passed through an 80-mesh sieve. The material passing through the sieve is collected, which is the first starch.

[0062] S104. After mixing the first starch and water evenly, the pH of the system is adjusted to 6.0±0.1 using 5% hydrochloric acid and 5% sodium hydroxide aqueous solution. Then, the mixture is stirred at a constant temperature of 53℃ and 60rpm for 8 minutes to obtain a first starch milk with a concentration of 8%.

[0063] S105. Add the mixture of α-amylase and saccharifying enzyme to the first starch milk and mix well. Stir at a constant temperature of 54℃ and 60 rpm for 20 min to obtain the enzymatic hydrolysate. The amount of α-amylase is 2.5 U / mg dry starch and the amount of saccharifying enzyme is 3.0 U / mg dry starch.

[0064] S106. Heat the enzymatic hydrolysate in a bath at 95°C for 15 minutes, then cool it to room temperature. Centrifuge at 3500 rpm for 12 minutes to obtain the second centrifugal precipitate. Wash the second centrifugal precipitate with anhydrous ethanol until no sugar residue remains. Then dry the washed second centrifugal precipitate in an oven at 58°C until constant weight. Crush the dried first centrifugal precipitate and pass it through an 80-mesh sieve. Collect the sieve residue, which is the second starch.

[0065] S107. After mixing the second starch and water evenly, adjust the pH of the system to 5.0±0.1 using 5% hydrochloric acid and 5% sodium hydroxide aqueous solution. Then, stir at a constant temperature of 43℃ and 60rpm for 8 minutes to obtain a second starch milk with a concentration of 8%.

[0066] S108. Mix the second starch milk and crosslinking agent (phosphorus oxychloride) evenly, and stir at 100 rpm for 1.2 h at a reaction temperature of 42℃. After the reaction is completed, adjust the pH of the reaction system to neutral with a 5% sodium hydroxide aqueous solution to obtain the crosslinking reaction solution. The amount of crosslinking agent is 0.10% of the dry starch in the second starch milk.

[0067] S109. The cross-linking reaction solution is heated in a bath at 95°C for 12 minutes, cooled to room temperature, and centrifuged at 3500 rpm for 12 minutes to obtain the third centrifugal precipitate. The third centrifugal precipitate is washed with anhydrous ethanol until no sugar residue is found. The washed third centrifugal precipitate is then dried in an oven at 58°C until constant weight. The dried first centrifugal precipitate is pulverized and passed through an 80-mesh sieve. The sieve-passing material is collected, which is the modified potato starch.

[0068] Example 2

[0069] A method for modifying potato starch, achieved through the following steps: S201. After mixing resistant potato starch and water evenly, the pH of the system is adjusted to neutral by using 15% hydrochloric acid and 15% sodium hydroxide aqueous solution. Then, the mixture is stirred at 50 rpm for 12 minutes at 42°C to obtain 12% resistant potato starch milk.

[0070] S202. Place the resistant potato starch milk in an ultrasonic processor, set the ultrasonic power to 400W, the ultrasonic frequency to 40kHz, and control the temperature of the resistant potato starch milk at 42℃. Under stirring conditions at 50rpm, ultrasonically treat for 32min to obtain ultrasonically treated starch milk.

[0071] S203. The ultrasonically treated starch milk is heated in a bath at 102°C for 15 minutes, then cooled to room temperature, and centrifuged at 4000 rpm for 8 minutes to obtain the first centrifugal precipitate. The first centrifugal precipitate is washed with anhydrous ethanol until no sugar residue is left, and then the washed first centrifugal precipitate is dried in an oven at 62°C until constant weight.

[0072] After drying, the first centrifuged precipitate is crushed and passed through an 80-mesh sieve. The material passing through the sieve is collected, which is the first starch.

[0073] S204. After mixing the first starch and water evenly, the pH of the system is adjusted to 6.0±0.1 using 15% hydrochloric acid and 15% sodium hydroxide aqueous solution. Then, the mixture is stirred at 50 rpm for 12 min at 57℃ to obtain a first starch milk with a concentration of 12%.

[0074] S205. Add the mixture of α-amylase and saccharifying enzyme to the first starch milk and mix well. Stir at a constant temperature of 50 rpm for 40 min at an enzymatic hydrolysis temperature of 56℃ to obtain the enzymatic hydrolysate. The amount of α-amylase is 2.0 U / mg dry starch and the amount of saccharifying enzyme is 2.8 U / mg dry starch.

[0075] S206. Heat the enzymatic hydrolysate in a bath at 102℃ for 10 minutes, then cool it to room temperature. Centrifuge at 4000 rpm for 8 minutes to obtain the second centrifugal precipitate. Wash the second centrifugal precipitate with anhydrous ethanol until no sugar residue remains. Then dry the washed second centrifugal precipitate in an oven at 62℃ until constant weight. Crush the dried first centrifugal precipitate and pass it through an 80-mesh sieve. Collect the sieve residue, which is the second starch.

[0076] S207. After mixing the second starch and water evenly, adjust the pH of the system to 5.0±0.1 using 15% hydrochloric acid and 15% sodium hydroxide aqueous solution. Then, stir at a constant temperature of 50 rpm for 12 minutes at 47℃ to obtain a second starch milk with a concentration of 12%.

[0077] S208. Mix the second starch milk and crosslinking agent (phosphorus oxychloride) evenly, and stir at 150 rpm for 0.8 h at a reaction temperature of 48°C. After the reaction is completed, adjust the pH of the reaction system to neutral with a 15% sodium hydroxide aqueous solution to obtain the crosslinking reaction solution. The amount of crosslinking agent is 0.20% of the dry starch in the second starch milk.

[0078] S209. The cross-linking reaction solution is heated in a bath at 102℃ for 8 minutes, cooled to room temperature, and centrifuged at 4000 rpm for 8 minutes to obtain the third centrifugal precipitate. The third centrifugal precipitate is washed with anhydrous ethanol until no sugar residue is left, and then dried in an oven at 62℃ to constant weight. The dried first centrifugal precipitate is pulverized and passed through an 80-mesh sieve. The sieve-passing material is collected, which is the modified potato starch.

[0079] Example 3

[0080] A method for modifying potato starch, achieved through the following steps: S301. After mixing resistant potato starch and water evenly, the pH of the system is adjusted to neutral by using 10% hydrochloric acid and 10% sodium hydroxide aqueous solution. Then, the mixture is stirred at 55 rpm for 10 minutes at 40°C to obtain 10% resistant potato starch milk.

[0081] S302. Place the resistant potato starch milk in an ultrasonic processor, set the ultrasonic power to 300W, the ultrasonic frequency to 30kHz, and control the temperature of the resistant potato starch milk at 40℃. Under stirring conditions, ultrasonically treat for 30 minutes to obtain ultrasonically treated starch milk.

[0082] S303. The ultrasonically treated starch milk is heated in a bath at 100°C for 18 minutes, then cooled to room temperature, and centrifuged at 3000 rpm for 10 minutes to obtain the first centrifugal precipitate. The first centrifugal precipitate is washed with anhydrous ethanol until no sugar residue is left, and then the washed first centrifugal precipitate is dried in an oven at 60°C until constant weight.

[0083] After drying, the first centrifuged precipitate is crushed and passed through an 80-mesh sieve. The material passing through the sieve is collected, which is the first starch.

[0084] S304. After mixing the first starch and water evenly, the pH of the system is adjusted to 6.0±0.1 using 10% hydrochloric acid and 10% sodium hydroxide aqueous solution. Then, the mixture is stirred at a constant temperature of 55℃ and 55rpm for 10min to obtain a 10% starch milk.

[0085] S305. Add the mixture of α-amylase and saccharifying enzyme to the first starch milk and mix well. Stir at a constant temperature of 55℃ and a speed of 55rpm for 30min to obtain the enzymatic hydrolysate. The amount of α-amylase is 2.3U / mg dry starch and the amount of saccharifying enzyme is 2.9U / mg dry starch.

[0086] S306. Heat the enzymatic hydrolysate in a bath at 95~102℃ for 12 min, then cool it to room temperature and centrifuge it at 3000 rpm for 10 min to obtain the second centrifugal precipitate. Wash the second centrifugal precipitate with anhydrous ethanol until no sugar residue remains, and then dry the washed second centrifugal precipitate in an oven at 60℃ until constant weight. Crush the dried first centrifugal precipitate and pass it through an 80-mesh sieve. Collect the sieve residue, which is the second starch.

[0087] S307. After mixing the second starch and water evenly, adjust the pH of the system to 5.0±0.1 using 10% hydrochloric acid and 10% sodium hydroxide aqueous solution. Then, stir at a constant temperature of 55 rpm for 10 min at 45℃ to obtain a second starch milk with a concentration of 10%.

[0088] S308. Mix the second starch milk and crosslinking agent (phosphorus oxychloride) evenly, and stir at 120 rpm for 1.0 h at a reaction temperature of 45℃. After the reaction is completed, adjust the pH of the reaction system to neutral with a 10% sodium hydroxide aqueous solution to obtain the crosslinking reaction solution. The amount of crosslinking agent is 0.15% of the dry starch in the second starch milk.

[0089] S309. The cross-linking reaction solution is heated in a bath at 100℃ for 10 minutes, cooled to room temperature, and centrifuged at 3000 rpm for 10 minutes to obtain the third centrifugal precipitate. The third centrifugal precipitate is washed with anhydrous ethanol until no sugar residue is found. The washed third centrifugal precipitate is then dried in an oven at 60℃ until constant weight. The dried first centrifugal precipitate is pulverized and passed through an 80-mesh sieve. The sieve-passing material is collected, which is the modified potato starch.

[0090] Comparative Example 1 The operation process is the same as steps S301~S303 in Example 3, to obtain the first starch.

[0091] The difference is that the ultrasonic power is selected as 100W.

[0092] Comparative Example 2 The operation process is the same as steps S301~S303 in Example 3, to obtain the first starch.

[0093] The difference is that the ultrasonic power is selected as 500W.

[0094] Comparative Example 3 The operation process is the same as steps S304~S306 in Example 3, to obtain the second starch.

[0095] The difference is that the enzymatic hydrolysis time is 10 minutes.

[0096] Comparative Example 4 The operation process is the same as steps S304~S306 in Example 3, to obtain the second starch.

[0097] The difference is that the enzymatic hydrolysis time is 50 minutes.

[0098] Comparative Example 5 The operation process is the same as steps S307~S309 in Example 3, to obtain modified potato starch.

[0099] The difference is that the amount of cross-linking agent used is 0.05% of the amount of dry starch used in the second starch milk.

[0100] Comparative Example 6 The operation process is the same as steps S307~S309 in Example 3, to obtain modified potato starch.

[0101] The difference is that the amount of cross-linking agent used is 0.25% of the amount of dry starch used in the second starch milk.

[0102] Experimental Example 1 Using resistant potato starch with a resistant starch content of 52.15% as raw material, modified potato starch was prepared according to the methods described in Examples 1-3 and Comparative Example 7. The modified potato starch was then tested for resistant starch content, thermal decomposition temperature, weight loss, shear stability, gelatinization temperature, gelatinization enthalpy, and water solubility. Each sample was measured in triplicate, and the average value was taken. The results are recorded in Table 1.

[0103] Detection method: Resistant starch content: enzymatic hydrolysis method, referring to GB / T 22224-2008 Determination of dietary fiber in food (enzyme gravimetric method and enzyme gravimetric method-liquid chromatography).

[0104] Water solubility / swelling capacity: Gravimetric analysis method, refer to GB / T 5009.3-2016 Determination of moisture in food and AACC Method 56-30.01 Determination of starch swelling power.

[0105] Gelatinization temperature: Differential scanning calorimetry, refer to ISO 11216:1998 (Determination of starch gelatinization properties).

[0106] Gelatinization enthalpy: Differential scanning calorimetry, refer to ASTM E793 (Standard Test Method for Thermal Analysis / Enthalpy of Melting and Crystallization).

[0107] Peak viscosity / shear viscosity / shear loss rate: completed using RVA (Rapid Viscosity Analyzer), referring to GB / T20377-2006 (Determination of Gelatinization Characteristics of Modified Starch); Peak viscosity: the maximum viscosity value reached during starch gelatinization; Shear viscosity: usually refers to the "holding viscosity" or "hot paste viscosity" under high temperature or high shear force; Shear loss rate: reflects the decrease in viscosity under high-temperature shear. The calculation formula is typically: (peak viscosity - holding viscosity) / peak viscosity × 100%, corresponding to the disintegration value concept in the RVA curve; the shear rate is set to 100 s during the test. -1 .

[0108] Thermal decomposition temperature / thermal weight loss rate: Thermogravimetric analysis, refer to ASTM E1131 (Standard test method for determining thermal decomposition temperature by thermogravimetric analysis).

[0109] Blank Example 1 is resistant potato starch with a resistant starch content of 52.15%, which is also the experimental raw material.

[0110] Table 1

[0111] As can be seen from the results in Table 1, the resistant potato starch prepared by the scheme of this application, compared with the raw material resistant potato starch (i.e., blank example 1), has an increased resistant starch content of about 45.9% or more, a decrease in shear viscosity loss rate of at least about 42.6%, an increase in water solubility of about 145.6% or more, an increase in thermal decomposition temperature of about 11.9%, a decrease in gelatinization temperature of at least about 6.5%, a decrease in gelatinization enthalpy of about 21.7%, and a decrease in weight loss rate of at least about 21.4%.

[0112] In the above examples, resistant starch content is one of the core indicators for evaluating the modification effect. It refers to the portion of starch that cannot be digested and absorbed in the human small intestine but can only be utilized by microorganisms in the large intestine, directly affecting the health benefits and application value of starch. A higher resistant starch content indicates a higher proportion of undigested and unabsorbed starch, which is more conducive to its health benefits. In this application, the resistant starch content increased from an initial 52.15±0.29% to approximately 77-80%, demonstrating a significant increase in resistant starch content in the product after modification using the method described in this application.

[0113] Thermal decomposition temperature is one of the indicators for measuring the thermal stability of starch. The higher the value, the better the thermal stability and heat resistance of starch. In this application, the thermal decomposition temperature of starch was increased from the initial 268±2℃ to 298~311℃, which is sufficient to show that the thermal stability and heat resistance of starch were significantly improved after modification by the method of this application.

[0114] Starch weight loss refers to the percentage reduction in mass of a starch sample due to moisture evaporation, component decomposition, or structural changes under specific conditions (such as heating, drying, enzymatic hydrolysis, or chemical treatment). This indicator is commonly used to evaluate the thermal stability, digestibility, processing performance, or bonding of starch in composite materials. The lower the value, the better the thermal stability of the product. In this application, the starch weight loss decreased from an initial 36.4 ± 0.4% to approximately 26-29%, indicating that the thermal stability of the starch significantly increased after modification using the method described in this application.

[0115] Shear viscosity loss rate reflects the shear resistance of a product; the lower the shear loss rate, the better the shear resistance. In this application, the shear viscosity loss rate of starch decreased from the initial 34.5±0.6% to 14~21%, demonstrating that the shear resistance of starch is significantly improved after modification using the method described in this application.

[0116] Gelatinization temperature refers to the temperature range at which starch undergoes irreversible expansion and crystal structure destruction when heated in water. The lower the gelatinization temperature, the easier the starch gelatinizes, and the better the food processing and consumption quality is generally. In this application, the gelatinization temperature of the starch was reduced from the initial 72.5±0.5℃ to 66~68℃. This demonstrates that the modification method described in this application significantly reduces the gelatinization temperature of the starch, making the product easier to gelatinize.

[0117] The enthalpy of gelatinization is the energy required to break down the crystalline structure of starch during the gelatinization process. It reflects the degree of orderliness of starch molecules and the ease with which the product gelatinizes. The lower the enthalpy of gelatinization, the less heat is absorbed during gelatinization, and the easier it is to gelatinize. In this application, the initial enthalpy of gelatinization of starch was reduced from 14.3±0.3 J / g to 10~13 J / g. This demonstrates that the enthalpy of gelatinization of starch is significantly reduced after modification using the method described in this application, making the product easier to gelatinize.

[0118] Water solubility is an important functional indicator of starch, reflecting its ability to dissolve in water. Its level directly affects the dispersibility and stability of starch in food processing. Higher water solubility indicates that the starch is easier to dissolve and disperse, which is beneficial for processing. In this application, the water solubility of starch was increased from an initial 10.12±0.20% to 24~27%, demonstrating that the modification method in this application significantly improves the water solubility of starch, making the product easier to dissolve and disperse.

[0119] Comparing the results of Comparative Example 7 with those of Example 3, when the raw materials were treated with ultrasound, followed by cross-linking and then enzymatic hydrolysis, the resistant starch content, thermal decomposition temperature, gelatinization enthalpy, and water solubility decreased to varying degrees, while the weight loss rate, shear viscosity loss rate, and gelatinization temperature increased to varying degrees. This is because: For reducing the content of resistant starch, the pre-crosslinked surface layer increases the initial gelatinization barrier, but since the interior is not crosslinked and strengthened, once the surface barrier is destroyed by heating, the internal structure quickly disintegrates, so the overall increase in gelatinization temperature is limited.

[0120] The reason for the decrease in thermal decomposition temperature may be that although the cross-linking first forms a surface network, it fails to fully penetrate into the interior to reinforce the loose porous framework formed after enzymatic hydrolysis. The amorphous region inside lacks chemical cross-linking protection and is more prone to main chain breakage at high temperatures. Its thermal stability is not as good as the product that is first enzymatically hydrolyzed to create pores and then cross-linked and penetrated.

[0121] The increase in weight loss is because the cross-linking inhibits the enzymatic hydrolysis from penetrating deeper into the particle, resulting in more unstable chain segments remaining inside the particle. During thermal degradation, these segments release more volatile small molecules, leading to an increase in weight loss.

[0122] The increased shear viscosity loss rate may be due to the fact that the surface barrier formed by prior cross-linking cannot effectively protect the internal structure of the particles. Under high shear force, the amorphous regions that are not reinforced by cross-linking break first, leading to the collapse of the overall framework, resulting in a viscosity loss rate that is significantly higher than that of the homogenized network formed by prior enzymatic hydrolysis and then cross-linking.

[0123] The slight increase in gelatinization temperature is because the first cross-linked surface layer raises the initial gelatinization barrier, but since the interior is not cross-linked and strengthened, once the surface barrier is destroyed, the internal structure quickly disintegrates, so the overall increase in gelatinization temperature is limited.

[0124] The decrease in gelatinization enthalpy is due to the fact that the cross-linking first hinders the formation and rearrangement of the ordered crystalline region during enzymatic hydrolysis, resulting in a reduction in the complete double helix structure in the product. This leads to a reduction in the area of ​​the endothermic peak reflecting the unwinding of the ordered structure, thus causing a decrease in gelatinization enthalpy.

[0125] The decrease in water solubility may be due to the fact that the cross-linking process consumes a large number of hydrophilic hydroxyl groups on the surface, forming a hydrophobic cross-linking layer. However, the subsequent enzymatic hydrolysis has limited decomposition of this hydrophobic layer, thus leading to a decrease in water solubility.

[0126] The above comparison also illustrates that, using the method of this application, ultrasound and enzymatic hydrolysis synergistically construct a loose porous framework and release short chains, enabling the raw material to rearrange and form crystalline regions during heat treatment. The subsequent uniform penetration of the cross-linking agent forms a three-dimensional network penetrating the interior of the particles, while simultaneously fixing the crystalline regions, thus significantly improving the overall processing performance of the raw starch. In contrast, the method in Comparative Example 7, which involves ultrasound followed by cross-linking and then enzymatic hydrolysis, results in cross-linking preceding enzymatic hydrolysis, forming only a surface barrier. This leads to limited enzymatic hydrolysis and uneven cross-linking, resulting in overall processing performance inferior to the method of this application.

[0127] Experiment Example 2 The following comparative experiment was conducted using resistant potato starch with a resistant starch content of 52.15%, as well as the first starch and the second starch prepared in Example 3 as raw materials.

[0128] In Comparative Examples 1 and 2, the raw material was resistant potato starch, and Blank Example 1 was the same as Experimental Example 1 above, that is, resistant potato starch.

[0129] The raw materials in Comparative Examples 3 and 4 were the first starch prepared in Example 3, and Blank Example 2 was the first starch prepared in Example 3.

[0130] The raw materials in Comparative Examples 5 and 6 were the second starch prepared in Example 3, and the blank example 3 was the second starch prepared in Example 3.

[0131] The resistant starch content, water solubility, swelling degree, gelatinization temperature, and peak viscosity of the first starches prepared in Examples 1-3 and Comparative Examples 1 and 2 were measured, and the results are recorded in Table 2: Table 2

[0132] Table 2 shows that the results of Comparative Examples 1 and 5 indicate that when the ultrasonic power is 100 W, the resistant starch content is only 55.78%, an increase of only 6.96% compared to blank example 1. This is because when the ultrasonic power is low, the ultrasonic energy is insufficient to effectively break the hydrogen bonds and crystalline structure between starch molecules, resulting in fewer amorphous regions on the surface of starch granules and a slow increase in resistant starch content. When the ultrasonic power is 500 W, the resistant starch content drops to 60.15%, a decrease of 11.96% compared to 300 W in Example 3. This indicates that excessively high ultrasonic energy can cause starch molecular chains to break, the crystalline structure to be excessively destroyed, and some resistant starch to be converted into digestible starch, leading to a decrease in resistant starch content.

[0133] The results of Comparative Example 1 showed that the water solubility was 12.35% at an ultrasonic power of 100W, indicating that insufficient ultrasonic power was not effective in breaking down resistant starch. However, the results of Comparative Example 2 showed that the water solubility reached 28.76% at an ultrasonic power of 500W. This is because excessive ultrasonic power disrupted the surface structure of too many starch granules, exposing starch molecular chains, increasing hydrophilic groups, and enhancing interactions with water, thus leading to a greater increase in water solubility.

[0134] Swelling degree reflects the ability of starch granules to absorb water and swell in water, and is closely related to the gelatinization characteristics of starch; the higher the swelling degree, the easier it is to gelatinize. Comparative Example 1 showed that at 100 W, the swelling degree increased by only about 0.3 mL / g, indicating that low-power ultrasound has insufficient influence on the starch structure, resulting in a minimal increase in swelling degree. Comparative Example 2 showed that even when the ultrasound power was increased to 500 W, the change in swelling degree was not significant. This is because once the ultrasound power reaches a certain level, the structure of the starch granules has been sufficiently destroyed, and the water absorption capacity reaches saturation; further increasing the power cannot further improve the swelling degree.

[0135] The results of Comparative Example 1 indicate that low-power ultrasonic treatment, due to insufficient energy, lacks the destructive force on starch molecules, resulting in a minimal decrease in gelatinization temperature. In contrast, the results of Comparative Example 2 show that excessively high ultrasonic power significantly disrupts the crystalline structure of starch, reduces the intermolecular forces, and thus significantly lowers the gelatinization temperature.

[0136] Peak viscosity reflects the consistency of starch paste and is related to the taste and processing characteristics of starch. Comparative Example 1 shows that low-power ultrasonic treatment, due to insufficient energy, results in poor starch dispersion, leading to a minimal increase in viscosity. However, Comparative Example 2 shows that at an ultrasonic power of 500 W, the peak viscosity actually decreases due to excessively high ultrasonic power. This is because excessively high ultrasonic power causes a large number of starch molecular chains to break down, subsequently leading to a decrease in viscosity.

[0137] The second starches prepared in Examples 1-3 and Comparative Examples 3 and 4 were tested for resistant starch content, gelatinization temperature, gelatinization enthalpy, peak viscosity, shear viscosity, and water solubility. The results are recorded in Table 3. Table 3

[0138] The results of Comparative Example 3 in Table 3 show that the resistant starch content was only 70.15% with insufficient enzymatic hydrolysis time (10 min), an increase of only 2.68% compared to the ultrasonically pretreated sample. This indicates that an excessively short enzymatic hydrolysis time cannot effectively degrade the digestible components in starch, resulting in a minimal increase in resistant starch content. Furthermore, the decrease in gelatinization temperature and enthalpy was also not significant, indicating that an excessively short enzymatic hydrolysis time is also not conducive to reducing the gelatinization temperature and enthalpy of starch. The results of Comparative Example 4 show that an excessively long enzymatic hydrolysis time (50 min) actually decreased the resistant starch content, dropping to 69.82% at 50 min, a decrease of 7.74% compared to 30 min. This indicates that an excessively long enzymatic hydrolysis time leads to excessive degradation of starch molecules by amylase, not only degrading digestible starch but also damaging the structure of resistant starch, resulting in a decrease in resistant starch content.

[0139] In Comparative Example 3, the water solubility was 24.35% when the enzymatic hydrolysis time was 10 min. This was because insufficient hydrolysis time resulted in insufficient exposure of hydrophilic groups in the starch structure, leading to a minimal increase in hydrophilicity. In contrast, Comparative Example 4 achieved 32.68% when the enzymatic hydrolysis time was 50 min. This was because excessively long hydrolysis times cause the enzymatic hydrolysis to excessively disrupt the starch granular structure, exposing more starch molecular chains, increasing the number of hydrophilic groups, and enhancing their interaction with water, thus increasing water solubility.

[0140] In Comparative Example 3, when the enzymatic hydrolysis time was 10 min, the peak viscosity was 3620 mPa·s, indicating that insufficient enzymatic hydrolysis time could not effectively degrade starch granules, resulting in a negligible decrease in peak viscosity. In contrast, in Comparative Example 4, when the enzymatic hydrolysis time was 50 min, the peak viscosity dropped to 2850 mPa·s. This is because excessively long enzymatic hydrolysis caused excessive breakage of starch molecular chains, reducing the molecular weight and significantly lowering the viscosity of the resulting starch paste.

[0141] Shear viscosity reflects the rheological properties of starch paste. The results of Comparative Example 3 show that insufficient enzymatic hydrolysis time has no significant effect on reducing shear viscosity. However, the results of Comparative Example 4 show that excessive enzymatic hydrolysis time (50 min) leads to a significant decrease in shear viscosity. This is because excessive enzymatic hydrolysis causes too many molecular chains in starch to be hydrolyzed into smaller fragments, resulting in a significant decrease in shear viscosity.

[0142] The resistant potato starches prepared in Comparative Examples 5 and 6 were tested for resistant starch content, thermal decomposition temperature, weight loss, shear stability, gelatinization temperature, gelatinization enthalpy, and water solubility. The results are recorded in Table 4.

[0143] Table 4

[0144] In Table 4, the results of Comparative Example 5 show that when the crosslinking agent dosage is 0.05%, there is no significant change in the physicochemical properties such as thermal decomposition temperature and weight loss rate. This is because when the crosslinking agent dosage is low, the degree of crosslinking within the starch molecules is insufficient, resulting in a small amount of stable structure that resists external heat and mechanical shearing. The results of Comparative Example 6 show that when the crosslinking agent dosage is 0.25%, the thermal decomposition temperature rises to 312℃, and the weight loss rate decreases to 25.8%. This is because the crosslinking agent forms stable covalent bonds between starch molecules, enhancing the structural stability of the starch molecules and reducing decomposition and weight loss at high temperatures.

[0145] The results of Comparative Example 5 show that when the amount of crosslinking agent is 0.05%, the amount of crosslinking agent is insufficient, the degree of crosslinking between starch molecules is low, and the structure of resistant starch cannot be fully fixed, resulting in a slow increase in resistant starch content. The resistant starch content is only 76.82%, which is only 1.51% higher than that of blank example 3. The results of Comparative Example 6 show that when the amount of crosslinking agent is 0.25%, the amount of crosslinking agent is excessive, and the starch molecules are over-crosslinked, forming a dense network structure. However, the resistant starch content no longer increases significantly. At this time, the resistant starch content is 79.12%, which is only 0.21% higher than that of example 3 in Table 1. This is because the crosslinking between starch molecules has reached saturation at this time, and further increasing the amount of crosslinking agent cannot increase the resistant starch content.

[0146] Mechanical stability is mainly evaluated through shear stability. Better shear stability means the starch is less prone to degradation and exhibits less viscosity change during high-shear processing. The sample in Comparative Example 5 was tested at a shear rate of 100 s⁻¹. -1 In Comparative Example 6, the viscosity loss rate was 24.5%, while in Comparative Example 7 it was reduced to 12.6%. This is because the cross-linked network structure can resist the action of shear force, reduce the breakage of starch molecular chains, and thus improve mechanical stability. In Comparative Example 8, due to the small amount of cross-linking agent, the degree of cross-linking within the starch molecules was insufficient, and the improvement on the mechanical stability of starch was limited.

[0147] Gelatinization temperature and enthalpy of gelatinization reflect the gelatinization characteristics of starch. The gelatinization temperature of blank example 3 was 63.2℃, and the enthalpy of gelatinization was 10.1 J / g. In contrast, the gelatinization temperature of comparative example 6 increased to 68.5℃, and the enthalpy of gelatinization increased to 12.3 J / g. This is because excessive cross-linking significantly enhanced the intermolecular forces of starch, making the starch granules more difficult to gelatinize and requiring higher temperatures and more heat. Comparative example 5 had a gelatinization temperature of 64.8℃ and an enthalpy of gelatinization of 10.6 J / g, which was due to insufficient cross-linking agent, resulting in inadequate enhancement of the intermolecular forces of starch.

[0148] Water solubility reflects the ability of starch to dissolve in water. The water solubility of blank sample 3 was 29.72%, while that of comparative sample 6 decreased to 24.35%. This is because the network structure formed by excessive cross-linking significantly limited the interaction between starch molecules and water, thus reducing the water solubility of starch. The decrease in water solubility of comparative sample 5 was not significant, indicating that insufficient cross-linking agent did not form a large number of network structures between starch particles, meaning its effect on water solubility was not significant.

[0149] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of this application, and are not intended to limit them. Although this application has been described in detail with reference to the foregoing embodiments, those skilled in the art should understand that modifications can still be made to the technical solutions described in the foregoing embodiments, or equivalent substitutions can be made to some or all of the technical features therein. Such modifications or substitutions do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of this application.

Claims

1. A method for modifying potato starch, characterized in that, Includes the following steps: Resistant potato starch with a resistant starch content >50% was mixed evenly with water and subjected to a first pre-dispersion to obtain resistant potato starch milk. The resistant potato starch milk was subjected to ultrasonic treatment and a first post-treatment in sequence to obtain the first starch. The first starch and water are mixed evenly and then pre-dispersed to obtain the first starch milk; The first starch milk was subjected to enzymatic hydrolysis and a second post-treatment in sequence to obtain the second starch. The second starch and water are mixed evenly, and a third pre-dispersion is performed to obtain the second starch milk; A cross-linking agent is added to the second starch milk to carry out a cross-linking reaction, followed by a third post-treatment to obtain modified potato starch. The enzymatic hydrolysis process is as follows: Add the enzyme preparation to the first starch milk and mix well. Stir at a constant temperature of 54-56℃ for 20-40 minutes to obtain the enzymatic hydrolysate. The enzyme preparation is a mixture of α-amylase and saccharifying enzyme, wherein the amount of α-amylase is 2.0~2.5 U / mg dry starch and the amount of saccharifying enzyme is 2.8~3.0 U / mg dry starch.

2. The method for modifying potato starch according to claim 1, characterized in that, The first pre-dispersion operation process is as follows: After mixing resistant potato starch and water evenly, the pH of the system is adjusted to neutral using an acid-base regulator, and then stirred at a constant temperature of 38-42℃ for 8-12 minutes to obtain resistant potato starch milk. The acid-base regulator is an aqueous solution of an inorganic acid and an inorganic base; The concentration of the resistant potato starch milk is 8-12%.

3. The method for modifying potato starch according to claim 1, characterized in that, The ultrasonic treatment process is as follows: The resistant potato starch milk was placed in an ultrasonic processor and ultrasonically treated for 28-32 minutes under stirring conditions to obtain ultrasonically treated starch milk. During the ultrasonic treatment, the ultrasonic power is 200~400w, the ultrasonic frequency is 20~40kHz, and the temperature of the resistant potato starch milk is controlled at 38~42℃.

4. The method for modifying potato starch according to claim 1, characterized in that, The first post-processing operation is as follows: The ultrasonically treated starch milk was heated in a bath at 95-102℃ for 15-20 minutes, then cooled to room temperature, and centrifuged at 3000-4000 rpm for 8-12 minutes to obtain the first centrifugal precipitate. The first centrifugal precipitate was washed with anhydrous ethanol until no sugar residue was found, and then dried in an oven at 58-62℃ until constant weight. After drying, the first centrifuged precipitate is crushed and passed through an 80-mesh sieve. The material passing through the sieve is collected, which is the first starch.

5. The method for modifying potato starch according to claim 1, characterized in that, The second pre-dispersion operation process is as follows: After mixing the first starch and water evenly, the pH of the system is adjusted to the first weak acidity using an acid-base regulator, and then stirred at a constant temperature of 53~57℃ for 8~12 minutes to obtain the first starch milk. The acid-base regulator is an aqueous solution of an inorganic acid and an inorganic base; The first weak acidity is pH = 6.0 ± 0.1; The concentration of the first starch milk is 8-12%.

6. The method for modifying potato starch according to claim 1, characterized in that, The second post-processing operation is as follows: Heat the enzymatic hydrolysate in a bath at 95-102℃ for 10-15 minutes, then cool it to room temperature. Centrifuge it at 3000-4000 rpm for 8-12 minutes to obtain a second centrifugal precipitate. Wash the second centrifugal precipitate with anhydrous ethanol until no sugar residue remains. Then dry the washed second centrifugal precipitate in an oven at 58-62℃ until constant weight. After drying, the first centrifuged precipitate is crushed and passed through an 80-mesh sieve. The material passing through the sieve is collected, which is the second starch.

7. The method for modifying potato starch according to claim 1, characterized in that, The third pre-dispersion operation process is as follows: After mixing the second starch and water evenly, the pH of the system is adjusted to a slightly acidic level using an acid-base regulator. Then, the mixture is stirred at a constant temperature of 43-47℃ for 8-12 minutes to obtain the second starch milk. The acid-base regulator is an aqueous solution of an inorganic acid and an inorganic base; The second weak acidity is pH = 5.0 ± 0.1; The concentration of the second starch milk is 8-12%.

8. The method for modifying potato starch according to claim 1, characterized in that, The operation process of the crosslinking reaction is as follows: The second starch milk and the crosslinking agent were mixed evenly and stirred at a reaction temperature of 42~48℃ for 0.8~1.2h. The pH of the reaction system was then adjusted to neutral with alkali to obtain the crosslinking reaction solution. The amount of the crosslinking agent used is 0.10~0.20% of the dry starch content in the second starch milk; The crosslinking agent is one or more of phosphorus oxychloride, malic acid, malonic acid, citric acid, and tartaric acid. The alkali is an inorganic alkali or an aqueous solution of an inorganic alkali; The third post-processing operation is as follows: The cross-linking reaction solution was heated in a bath at 95-102℃ for 8-12 minutes, cooled to room temperature, and centrifuged at 3000-4000 rpm for 8-12 minutes to obtain the third centrifugal precipitate. The third centrifugal precipitate was washed with anhydrous ethanol until no sugar residue was found, and then dried in an oven at 58-62℃ until constant weight. After drying, the first centrifuged sediment is crushed and passed through an 80-mesh sieve. The material passing through the sieve is collected, which is the modified potato starch.

9. A modified potato starch, characterized in that, It is prepared by the method described in any one of claims 1 to 8.